(untitled) (Economic and Political Thought, 2015)
Changes introduced by the Treaty of Lisbon resulted in a substantial shift of vote strength between the member states of the Council of the European Union. It also had great influence on the position of Poland and its bargaining power in this institution. Although the Treaty modified only the formal determinants of strength, it changed the dynamics of the decisionmaking process as well as the importance of the European Commission, the European Parliament and the Council of the European Union in this process. The article highlights the new way of weighing votes in the Council of the EU, the increase in the scope of decisions taken by qualified majority and the introduction of new competences clauses, which had impact on the position of Poland in this institution. It shows a substantive shift of vote strength towards the four biggest member states at the expense of countries with smaller population. As a result, it will be more difficult for Poland to build its bargaining power based on formal-legal factors. Thus, the skills in multi-level and parallel negotiations, presenting own interests, reliable and consistent arguments, and promotion of common initiatives will become more important. The work makes a wide use of multiplayer voting games, especially mathematical indexes of strength in order to demonstrate its flow between the members of the Council of the EU. The author also uses a formal-dogmatic method in order to analyse the contents of the source materials, including mainly the primary legal acts. The mathematical indexes of strength, for the needs of the analysis presented in the article, were calculated with the use of the program POWERGEN 1.0.